On distance magic Harary graphs - Prajeesh A.V.; Paramasivam K.; Kathiresan K.M. (Utilitas Mathematica, 2020)
This paper establishes two new techniques to construct larger distance magic and (a, d)-distance antimagic graphs using Harary graphs and provides a solution to the existence of distance magicness of G o C4 and G × C4, for every non-regular distance magic graph G with maximum degree |V(G)| - 1. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.